Study of Composition and Surface Morphology of Seaweed as Biosorbent: A Review - N Mingu; S A Aziz; E Y Stidi; Mohd Hafiz Abd. Majid; J Idris; Mohd Sani bin Sarjadi (2022)
Heavy metal contamination is harmful to living creatures and deteriorate environment. Adsorption of heavy metal by biomass as adsorbent been the best alternative for heavy metal removal. Despite abundance of biomass as biosorbent, approach on adsorption by seaweed been studied because of its prominence benefits such as accessibility, minimal cost and ease of use. Some metal can be accumulated by seaweed without causing any hazardous by product. Thus, sorption of heavy metal by seaweed as biosorbent is studied. In this article, relationship between adsorption of heavy metal ions with composition and surface morphology of seaweeds are reviewed. Tables used to summarise the difference of composition and morphology of seaweed after treated with metal.